2011
DOI: 10.1111/j.1475-4959.2011.00411.x
|View full text |Cite
|
Sign up to set email alerts
|

Using GIS and perceived distance to understand the unequal geographies of healthcare in lower‐income urban neighbourhoods

Abstract: Geographers play important roles in public health research, particularly in understanding healthcare accessibility, utilisation, and individual healthcare experiences. Most accessibility studies have benefited from the increased sophistication of geographic information systems (GIS). Some studies have been enhanced with semi-structured in-depth interviews to understand individual experiences of people as they access healthcare. However, few accessibility studies have explicitly utilised individual in-depth int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
63
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(65 citation statements)
references
References 59 publications
1
63
0
1
Order By: Relevance
“…[56,57]), this study has shown that these perceived walking times/distances are often an overestimation of the objective walking times/distances. Future studies should keep this poor correspondence in mind, as well as the fact that when only using self-reported walking times, the results can be influenced by physical activity and other variables.…”
Section: Discussionmentioning
confidence: 97%
“…[56,57]), this study has shown that these perceived walking times/distances are often an overestimation of the objective walking times/distances. Future studies should keep this poor correspondence in mind, as well as the fact that when only using self-reported walking times, the results can be influenced by physical activity and other variables.…”
Section: Discussionmentioning
confidence: 97%
“…With the advent and evolution of statistical and computer sciences and the greater availability of medical and epidemiological data, it gave rise to medical GIS, which has integrated statistical and spatial analysis functions. GIS has been used descriptively in population and public health fields (Ogden et al, 2014; Moore et al, 2008; Ricketts, 2003) to examine healthcare service provision (Hawthorne and Kwan, 2012) and epidemiology (Clarke et al, 1996). …”
Section: Project-based Experiential Learning Using Gis and Sas Technimentioning
confidence: 99%
“…Additionally data intensive scientific analyses (Park and VanRoekel, 2013; Ailamaki et al, 2010) that merge visualization and workflow technologies have become especially important aspects to sort large quantities of available biological data; Big Data (United States Census Bureau, University of Wisconsin Population Health Institute). Mature spatial analysis GIS applications on the Environmental Systems Research Institutes (ESRIs) ArcGIS suites and SAS techniques developed by the SAS Institute are found to be useful in integrating optimal search strategies and are powerful evidence-based practice tools in the domain of public health (Ogden et al, 2014; Duncan et al, 2014; Musa et al, 2013; Hawthorne and Kwan, 2012; Moore et al, 2008; Ricketts, 2003; Lee and Wong, 2001; Clarke et al, 1996). …”
Section: Introductionmentioning
confidence: 99%
“…The role of distance is clearly important here, both physical ) and cognitive (e.g. Hawthorne & Kwan 2012). In addition, while we know the time available to an individual affects gambling outcomes (Baker & Marshall 2005), we know little about the temporal sequencing of gambling behaviour and the way it fits into daily spatial patterns.…”
mentioning
confidence: 98%